Spiral Ouroboros: Metasimulacrum in Rock and Metal Electric Guitar Processing and Modeling Technologies - Sergio Miranda-Bonilla (INSAM)
The article reviews Jean Baudrillard’s concept of simulacrum and puts it in dialogue with the evolution of signal processing technologies for electric guitar, introducing the concept of metasimulacrum—a simulacrum of a simulacrum—to describe the historical trajectory from early electric guitar amplification to recent advances in digital signal processing, taking a critical stance on technological determinism